Innovative higher education curriculum design towards creating sustainable and competitive employees - Daud S.; Abidin N.; Sapuan N.M.; Rajadurai J. (International Business Information Management Association, IBIMA, 2023)
This study attempts to investigate the gap between the important elements of Higher Education Institutions' graduates' attributes and their actual performance when employed by industry. The dimensions of attributes and the performance of these graduates are considered in four broad areas, namely knowledge, skills, abilities and personality. Data was collected using a structured questionnaire distributed to Human Resource Managers or supervisors of the graduates in 1000 top companies in Malaysia. The results show that the graduates' performance failed to meet managers' perceptions of the importance attributes that should be possessed by these graduates. Therefore, the Higher Education Institutions should take prompt action to review the current curriculum in order to meet industry demands and to produce employable graduates. Curriculum design should be directed towards attributes that are expected of the graduates and relevant to the industry and market needs. It will allow for corrective actions and improve perceived problem areas that covered all four dimensions.